2015
DOI: 10.1590/2359-3997000000045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycemic index on obesity control

Abstract: Objective: Evaluate the effect of glycemic index (GI) on biochemical parameters, food intake, energy metabolism, anthropometric measures and body composition in overweight subjects. Materials and methods: Simple blind study, in which nineteen subjects were randomly assigned to consume in the laboratory two daily low GI (n = 10) or high GI (n = 9) meals, for forty-five consecutive days. Habitual food intake was assessed at baseline. Food intake, anthropometric measures and body composition were assessed at each… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 24 publications
(23 reference statements)
1
15
0
2
Order By: Relevance
“…The results of a 10-week crossover study demonstrated that when subjects consumed a 56 g of almonds each day, they compensated for the energy provided by the almonds and reduced their food intake from other sources [ 11 ]. The effect on visceral body fat among the subjects in the PM group might suggest that almond consumption as a preload before the meal may be related with the insulin metabolism, which could be a topic of further studies, because body fat reduction in the abdominal region facilitates glycemic control [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…The results of a 10-week crossover study demonstrated that when subjects consumed a 56 g of almonds each day, they compensated for the energy provided by the almonds and reduced their food intake from other sources [ 11 ]. The effect on visceral body fat among the subjects in the PM group might suggest that almond consumption as a preload before the meal may be related with the insulin metabolism, which could be a topic of further studies, because body fat reduction in the abdominal region facilitates glycemic control [ 18 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several dietary interventions were designed to compare low GI or GL diets with their high GI or GL counterparts using crossover [ 18 , 62 , 63 , 64 , 65 ] or parallel [ 24 , 38 , 66 , 67 , 68 , 69 , 70 ] randomized designs ( Table 7 ). Among these studies, those with a crossover design were shorter in duration (10 days to 5 weeks per intervention phase), whereas parallel design interventions ranged from 45 days to 12 months in duration.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
“…Among these studies, those with a crossover design were shorter in duration (10 days to 5 weeks per intervention phase), whereas parallel design interventions ranged from 45 days to 12 months in duration. Studies included adults with type 2 diabetes [ 66 , 67 , 68 , 70 ], healthy adults with diverse weight status [ 65 ], or overweight and/or obese but otherwise healthy adults [ 18 , 24 , 38 , 62 , 63 , 64 , 69 ]. Reports from interventions involving nutrition education in which the use of GI was compared to current dietary recommendations for patients with type 2 diabetes (e.g., American Diabetic Association guidelines [ 71 ]) were excluded from this review because participants in different treatment arms were given different diet recommendations, which resulted in diets with multiple incomparable factors aside from the GI or GL of the diet.…”
Section: Glycemic Index/glycemic Load and Cardiometabolic Disease mentioning
confidence: 99%
See 1 more Smart Citation
“…Although biomechanical factors such as elevated BMI have been noted to play a role in knee and hand OA, some studies suggest that metabolic dysfunction in particular, as evidenced by elevated HgA1c levels, may play an even greater role in accelerated OA progression compared to weight alone [32][33][34]. Therefore, specific dietary recommendations should focus on reducing intake of foods with a high glycemic index [35] (potatoes, rice, sugar, processed foods, and foods with high trans-fat) and increasing intake of proteins, fruits, vegetables, monounsaturated fats (such as olive oil), and polyunsaturated fats (like flaxseed oil). Olive oil especially has demonstrated some evidence of reducing cartilage degeneration when combined with exercise [36].…”
Section: Weight Loss/diet Interventionsmentioning
confidence: 99%